Multichromosomal Mitochondrial Genome of Paphiopedilum micranthum: Compact and Fragmented Genome, and Rampant Intracellular Gene Transfer - Jia-Xing Yang; Nicolas Dierckxsens; Mingzhu Bai; Yanyan Guo (2023)
Orchidaceae is one of the largest families of angiosperms. Considering the large number of species in this family and its symbiotic relationship with fungi, Orchidaceae provide an ideal model to study the evolution of plant mitogenomes. However, to date, there is only one draft mitochondrial genome of this family available. Here, we present a fully assembled and annotated sequence of the mitochondrial genome (mitogenome) of Paphiopedilum micranthum, a species with high economic and ornamental value. The mitogenome of P. micranthum was 447,368 bp in length and comprised 26 circular subgenomes ranging in size from 5973 bp to 32,281 bp. The genome encoded for 39 mitochondrial-origin, protein-coding genes; 16 tRNAs (three of plastome origin); three rRNAs; and 16 ORFs, while rpl10 and sdh3 were lost from the mitogenome. Moreover, interorganellar DNA transfer was identified in 14 of the 26 chromosomes. These plastid-derived DNA fragments represented 28.32% (46,273 bp) of the P. micranthum plastome, including 12 intact plastome origin genes. Remarkably, the mitogenome of P. micranthum and Gastrodia elata shared 18% (about 81 kb) of their mitochondrial DNA sequences. Additionally, we found a positive correlation between repeat length and recombination frequency. The mitogenome of P. micranthum had more compact and fragmented chromosomes compared to other species with multichromosomal structures. We suggest that repeat-mediated homologous recombination enables the dynamic structure of mitochondrial genomes in Orchidaceae.